Preliminary phytochemical screening and hepatoprotective activity of methanol extract of Artocarpus hirsutus leaves. - Jitendra Patel; Venkateshwar Reddy; GS Kumar (International Journal of Phytomedicine, 2015)
The objective of the present work was investigating the preliminary phytochemical screening and hepatoprotective activity of methanol extract of the leaves of Artocarpus hirsutus. Group I served as vehicle control, Group II served CCL4 (2ml/kg, s.c.), Group III served as standard Silymarin (50 mg/kg, p.o.) Group IV and V served as methanolic extracts of Artocarpus hirsutus (MEAH) at the dose level (250 and 500 mg/kg, p.o.). The degree of protection was determined by measuring level biochemical marker like alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), direct bilirubin, total bilirubin and Cholesterol. The histopathology study also showed the hepatic protection of extracts. The preliminary phytochemical screening was performed to find out the phytoconstituents responsible for the activity. The marker biochemical level such as ALT, AST, ALP, Direct bilirubin, Total bilirubin and Cholesterol were significantly raised in CCL4 treated rats when compared with the normal group (p<0.05), but the MEAH (500 mg/kg, bw) treated rats exhibited maximum depletion. The histopathology study also showed the hepatic protection of extracts. Preliminary phytochemical screening showed the presence of glycosides, flavonoids, Tannins, triterpenoids, carbohydrates and steroids. The results of in vivo hepatoprotective activity showed that the methanol extract of Artocarpus hirsutus exhibit significant hepatoprotective activity. This might be due to flavonoids and tannins; which was confirmed their presence in phytochemical tests.